2013
DOI: 10.7224/1537-2073.2012-043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fatigue and Cognition in Patients with Relapsing Forms of Multiple Sclerosis Treated with Natalizumab

Abstract: Fatigue and cognitive impairment are debilitating features of multiple sclerosis (MS). ENER-G was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
(47 reference statements)
2
24
0
Order By: Relevance
“…Since these symptoms are absolutely rare in MS, their appearance in MS patients treated with NTZ should be considered as a red flag and should give rise to a suspicion of PML, thus prompting a rapid MR scan. Indeed, evidences are now available regarding the positive effects of NTZ on cognitive deterioration of MS patients over long follow ups, as well as on cognitive improvement of MS patients treated with NTZ over time [15][16][17][18][19][20][21]. Furthermore, a rebound of cognitive impairment has also been described following natalizumab discontinuation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Since these symptoms are absolutely rare in MS, their appearance in MS patients treated with NTZ should be considered as a red flag and should give rise to a suspicion of PML, thus prompting a rapid MR scan. Indeed, evidences are now available regarding the positive effects of NTZ on cognitive deterioration of MS patients over long follow ups, as well as on cognitive improvement of MS patients treated with NTZ over time [15][16][17][18][19][20][21]. Furthermore, a rebound of cognitive impairment has also been described following natalizumab discontinuation [22].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]29,30 Improvement occurred rapidly and was significant by the third month. Improvement in sleepiness, as measured by the ESS, was also observed.…”
Section: Mood and Cognitionmentioning
confidence: 93%
“…In the ENER-G (Evaluation of Natalizumab for thE Relief of MS Associated FatiGue) study, significant improvement in scores on fatigue scales was noted within 12 weeks, and this benefit persisted during the 48-week study. 15 Likewise, the TYNERGY study found that patients with MS reported significantly less fatigue after 12 months of natalizumab treatment. 16 Furthermore, the TYNERGY study found improvements in cognition, mood, and quality of life.…”
Section: Evaluationsmentioning
confidence: 98%
“…Another disease-modifying therapy, natalizumab, also appears to demonstrate improvements in fatigue. The ENER-G study showed benefi ts in patients with fatigue over the course of 1 year which remained stable for up to 48 weeks [ 187 ]. In the TYNERGY study, patients also had signifi cant improvements in fatigue measured over the course of 12 months, as well as in quality of life, sleepiness, depression, and cognition [ 188 ].…”
Section: Medication Therapiesmentioning
confidence: 99%